Synthesis and spectral characterization of some metal complexes containing azo derived from 2-aminobenzimidazole - Moslem Hassan Mohamed; Haitham Khadim Dakhil (Al-Qadisiyah Journal of Pure Science, 2017)
New complexes of 2[(2- Benzimidazole) azo] -4- Bromo aniline (BIABA) with Co(II), Ni(II), Cu(II), Zn(II) and Ag(I) were synthesized and characterized by infrared and electronic spectra and in addition of elemental analysis, molar conductance and magnetic susceptibility measurements. The data show that the ligand a bidentate and tridendate and coordinates of the metal ion via the group amine, nitrogen atom of azo and with imidazole (N3) atom. Octahedral environment is suggested for Co(II), Ni(II) Cu(II), Zn(II) metal complexes and tetrahedral for Ag(I) complex. The analytical data show that the metal to ligand ratio (M:L) in all complexes is (1:2) but Ag(I) is (1:1) .